The Effect of Service Quality Dimensions on Customer Satisfaction at Auto Bridal Carwash Malang - Fathur Rahman; Radityo Putro Handrito (Jurnal Ilmiah Mahasiswa FEB, 2015)
This study aims to examine the Effect of Service Quality on Customer Satisfaction at Auto Bridal Car Wash Malang. The regression analysis, Ftest and t test, were conducted in order to reveal the role of the independent variables (Physical aspect, Reliabiliy, Personal Interaction, Problem Solving, and Policy) on Customer Satisfaction. This study is explanatory research, in accordance with its purpose to describe the casual relationship among variables through hyphothesis testing. The samples and population of this study were the customers of Auto Bridal Car Wash in Malang. In this study, the data collection method is conducted through questionnaire distribution. The sampling technique used in this research is purposive sampling. Next, the research instrument were checked for its validity, reliability, and classical assumption. The hypotheses testing used F test and t Test in Multiple Regression Analysis. The multiple regression analysis showed that Physical aspect, Reliability, Personal Interaction, Problem solving, and Policy simultaneously brought significant effect on Customer Satisfaction. Further, the partial test indicate that all of variable significantly influence Customer Satisfaction. The dominant test demonstrates that Problem Solving causes dominant effect on customer satisfaction.  Keywords: physical aspect, reliability, personal interaction, problem solving, policy, customer satisfaction.